Tinjauan Perilaku Destruktif Perokok Aktif Terhadap Kawasan Tanpa Rokok Di Indonesia Dalam Perspektif Hukum Pidana Dan Hukum Islam - Tauratiya, Tauratiya (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2022)
The background of this problem is the rampant of destructive behavior of smokers which causes restlessness in the community. Cigarettes are not a taboo in society, especially the people of Indonesia. Cigarettes can be categorized as addictive substances that can cause addiction for the consumer. Not only addiction, there are many bad things such as damaging health that can be caused by smoking. Besides that, smokers usually often use cigarettes in public places if the smoke can disturb the surrounding community. Even though it has been explained about the area where there is no smoke. In fact, this has been regulated in the Indonesian Criminal Law as evidence that the government is very serious in responding to this matter. In the realm of Islamic law, there are already other provisions regarding to this matter. Although it is not explained in detail about smoking, it can still be likened to other things such as khamr. The destructive behavior of active smokers can disturb the surrounding community so that criminal law enforcement and Islamic law can be applied to violators of these rules. This is to create a situation where the general public is not disturbed by the destructive behavior of smokers.